Assessment of diarrhea treatment and counseling in community pharmacies in Baghdad, Iraq: A simulated patient study - Ibrahim IR; Palaian S; Ibrahim MI (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Because community pharmacists are the most accessible healthcare professionals, they are often involved in managing minor ailments within the community setting. Objective: This study evaluated the community pharmacists' history taking practice, medicine dispensing and advice in response to acute diarrhea. Methods: Authors conducted a simulated-patient study in 75 community pharmacies in Baghdad, Iraq from February to May 2015. The female simulated-patient complained of acute diarrhea that had lasted for one day and requested for medicine to treat her condition. After exiting each pharmacy, she then assessed the practices of the community pharmacists through the use of a specially designed checklist adopted with modifications from relevant guidelines. For history taking, a maximum total of eight was the highest obtainable score. Data collected was quantitatively analyzed and Mann-Whitney, Chi-square or Fishers exact tests were used at an alpha level of 0.05. Results: All of the 75 pharmacies visited were managed by professionally qualified pharmacists. The most common questions asked during history taking were number of diarrheal episodes (n=62; 82.7%); duration of symptoms (n=59; 78.7%) and presence of other diseases and if any drug had been taken (n=58; 77.3%). Female pharmacists had a higher total mean score (6.45, SD=1.33) for history taking when compared to their male counterparts (4.34, SD=2.13); p <0.001. Medicine combination of diphenoxylate HCl 2.5mg + atropine sulphate 0.025mg (n=34; 27.9%) was most frequently dispensed while the least was oral rehydration salt (n=1; 0.8%). Around 20% (n=15) of pharmacists dispensed antimicrobial agents. Over half (n=46; 61.3%) of pharmacists indicated the frequency of use on the medicine packet. Conversely, less than half (n=33; 44.0%) gave any advice on food and fluid intake. Conclusions: Majority of the community pharmacists asked at least four questions while taking patient history and was very likely to recommend antidiarrheal medicines as first line treatment options. The authors recommend the development of a minimum standard of practice as well as enhanced training for Iraqi community pharmacists.